Pengaruh Promosi Dan Lokasi Terhadap Keputusan Konsumen Dalam Menggunakan Jasa Pengiriman Barang Indah Cargo Di Kota Pariaman - Sudirman, Sudirman (CV. ITTC INDONESIA, 2023)
Indah Logistik Cargo is a service company engaged in the delivery of goods. The business of goods delivery services is one of the business fields that plays an important role in the economic system, because the service sector aims to serve the needs and desires of all people who need it. The purpose of this study was to determine the effect of price and location on service consumer decisions at Indah Logistik Cargo, Pariaman City. The type of research used in this study is quantitative, while the data used is primary data collected from respondents. The sampling technique in this research is incidental sampling technique, then processed with SPSS release 20.0 for windows program. The analysis used is multiple linear regression analysis where Price, and Location as independent variables and Consumer Decisions as dependent variables. The results of the research conducted indicate that from the results of the Simultaneous Test (Test F) it is known that the price and location variables simultaneously have a significant effect on consumer decisions in using goods delivery services at PT. Indah Cargo Kota Pariaman, Meanwhile, based on the results of the Partial Test (Test T) it is known that the price, and location partially have a significant effect on consumer decisions in using freight forwarding services at PT. Beautiful Cargo City Pariaman. Meanwhile, based on the calculation of the coefficient of determination (R2), the Adjusted R Square value is 0.574. This shows that together price, and location have a significant influence on consumer decisions in using freight forwarding services at PT. Indah Cargo Kota Pariaman by 57.4%. While the remaining 42.6% is influenced by other variables that are not examined in this study.